Ultrasound enhanced electrochemical oxidation of Alizarin Red S on boron doped diamond(BDD) anode:Effect of degradation process parameters. (October 2018) - Zhu, Chengwu; Jiang, Chuqi; Chen, Shou; Mei, Ruiqiong; Wang, Xin; Cao, Jun; Ma, Li; Zhou, Bo; Wei, Qiuping; Ouyang, Guangqi; Yu, Zhiming; Zhou, Kechao
Abstract: Textile wastewater is characterized by high toxicity, complex structure, and resistance to biodegradation. Therefore, advanced oxidation technologies have received extensive attention. However, it is usually difficult to achieve a desired degradation effect using a single technology. The combination of various advanced oxidation technologies is an important way to achieve efficient degradation of organic wastewater. The present investigation was focused on ultrasound enhanced electrochemical oxidation (US-EO) of typical anthracene Alizarin Red S dye on a boron doped diamond anode. Our work indicates that ultrasonic oxidation technology which is mainly based on cavitation, can produce strongly oxidizing active substances such as OH, HO2, O, and H2 O2, that accelerate the destruction of the dye molecular structure and achieve dye decolorization and mineralization. The effects on cavitation and decomposition of ARS by the parameters that affect degradation, including solution temperature, initial pH, and electrolytes, were examined. Results show that low temperature was more conducive to ultrasonic cavitation in the US-EO process; the degradation efficiency rate of EO was higher than that of US-EO when the solution temperature was above 45 °C. Ultrasonic cavitation was significantly more efficient in acid than in alkaline conditions. Almost 100% color removal and 86.07% COD removal was achieved for 100 mg L −1 ARS concentration with a 0.05 M Na2 SO4 electrolyte, temperature of 30 °C and pH of 4.97 after 3 h. GC-MS analysis showed that the intermediate products of ARS in the US-EO process were phthalic anhydride, PEAs and bisphenol A, which is eventually mineralized to CO2 and H2 O. Highlights: Degradation of ARS by US-EO technology is studied for the first time. Ultrasound based on cavitation can increase the mineralization rate of ARS. Lower temperatures are more beneficial for ultrasonic cavitation. Acidic conditions better promote the mineralization of ARS in the US-EO process. The intermediate products of ARS in the US-EO process were studied.